1993
DOI: 10.1172/jci116308
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms by which glucose can control insulin release independently from its action on adenosine triphosphate-sensitive K+ channels in mouse B cells.

Abstract: Glucose stimulation of insulin release involves closure of ATPsensitive K+ channels (K+-ATP channels), depolarization, and Ca" influx in B cells. However, by using diazoxide to open K+-ATP channels, and 30 mM K to depolarize the membrane, we could demonstrate that another mechanism exists, by which glucose can control insulin release independently from changes in K+-ATP channel activity and in membrane potential (Gembal et al. 1992. J. Clin. Invest. 89:1288-1295). A similar approach was followed here to invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
204
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(219 citation statements)
references
References 35 publications
11
204
0
Order By: Relevance
“…In the diazoxide experiments, the cells, in presence of 250 μmol/l diazoxide and 30 mmol/l KCl, were stimulated with 2.5 mmol/l glucose and then with 15 mmol/l glucose. The second incubation at 15 mmol/l glucose, reflecting the amplifying effect of the sugar on insulin secretion [22], was significantly reduced in REST-expressing INS-1E cells (ESM Fig. 1a).…”
Section: Resultsmentioning
confidence: 98%
“…In the diazoxide experiments, the cells, in presence of 250 μmol/l diazoxide and 30 mmol/l KCl, were stimulated with 2.5 mmol/l glucose and then with 15 mmol/l glucose. The second incubation at 15 mmol/l glucose, reflecting the amplifying effect of the sugar on insulin secretion [22], was significantly reduced in REST-expressing INS-1E cells (ESM Fig. 1a).…”
Section: Resultsmentioning
confidence: 98%
“…Glucose also has a stimulatory effect on insulin secretion independent of the K ATP channel. This pathway can be studied by keeping the K ATP (18,19). The K ATP channel-independent glucosesignaling pathway has been demonstrated also in human islets (23).…”
Section: Introductionmentioning
confidence: 99%
“…Glucose can augment insulin secretion independently of K + channel closure, provided that the cytoplasmic free Ca 2+ concentration is elevated (Gembal et al, 1992). A role for phospholipase C (PLC) in this phenomenon has been both claimed (Turk et al, 1993;Zawalich and Zawalich, 1997) and refuted (Gembal et al, 1993;Vadakekalam et al, 1997). Kelly et al (1994) suggested that the enhanced phosphoinositide (PI) response was partially Ca 2+ -dependent and might involve activation of distinct isozymes of PLC expressed in the islets.…”
Section: Introductionmentioning
confidence: 99%
“…However, current information about the cellular localization of PLC isozymes has so far been mainly limited to the brain and related organs (Ross et al, 1989;Peng et al, 1997). Therefore the pancreatic islet appears to be an interesting region in which to study the distribution of PLC isozymes mainly to provide clues to solving the controversy concerning the role of PLC isozymes in insulin secretion (Gembal et al, 1993;Vadakekalam et al, 1997). Moreover, several protein kinase C (PKC) isozymes, the downstream molecules for the PLC signaling pathway, were found from mouse pancreatic islets (Knutson and Hoenig, 1997).…”
Section: Introductionmentioning
confidence: 99%